2001
DOI: 10.1094/mpmi.2001.14.4.508
|View full text |Cite
|
Sign up to set email alerts
|

Apple Contains Receptor-like Genes Homologous to the Cladosporium fulvum Resistance Gene Family of Tomato with a Cluster of Genes Cosegregating with Vf Apple Scab Resistance

Abstract: Scab caused by the fungal pathogen Venturia inaequalis is the most common disease of cultivated apple (Malus x domestica Borkh.). Monogenic resistance against scab is found in some small-fruited wild Malus species and has been used in apple breeding for scab resistance. Vf resistance of Malus floribunda 821 is the most widely used scab resistance source. Because breeding a high-quality cultivar in perennial fruit trees takes dozens of years, cloning disease resistance genes and using them in the transformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
118
0
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(122 citation statements)
references
References 29 publications
1
118
0
3
Order By: Relevance
“…The presence of resistance gene Rvi6 (Vinatzer et al 2001) in local cultivars that showed high resistance to apple scab and fire blight (cultivars 1.1.9, 1.1.20, 2.1.1, 2.1.14, 2.1.21, 3.1.50, 3.1.75, 3.1.80, 3.1.87, 3.1.100, 5.1.23, 5.1.66) was investigated by PCR amplification using the Rvi6-specific primers T1-For (5 0 -CA-ATGCCTTACGTGGTGAAA-3 0 ) and RT2-Rev (5 0 -CAGGGATTCCAGCCAATCTA-3 0 ) at a final concentration of 0.8 lM. The PCR reactions contained 50 ng of purified plant genomic DNA (Lodhi et al 1994) and consisted of one cycle of 10 min at 94°C, followed by 35 cycles of 94°C for 1 min, 58°C for 1 min and 72°C for 2 min, finishing with a cycle of 10 min at 72°C.…”
Section: Pcr Analysesmentioning
confidence: 99%
“…The presence of resistance gene Rvi6 (Vinatzer et al 2001) in local cultivars that showed high resistance to apple scab and fire blight (cultivars 1.1.9, 1.1.20, 2.1.1, 2.1.14, 2.1.21, 3.1.50, 3.1.75, 3.1.80, 3.1.87, 3.1.100, 5.1.23, 5.1.66) was investigated by PCR amplification using the Rvi6-specific primers T1-For (5 0 -CA-ATGCCTTACGTGGTGAAA-3 0 ) and RT2-Rev (5 0 -CAGGGATTCCAGCCAATCTA-3 0 ) at a final concentration of 0.8 lM. The PCR reactions contained 50 ng of purified plant genomic DNA (Lodhi et al 1994) and consisted of one cycle of 10 min at 94°C, followed by 35 cycles of 94°C for 1 min, 58°C for 1 min and 72°C for 2 min, finishing with a cycle of 10 min at 72°C.…”
Section: Pcr Analysesmentioning
confidence: 99%
“…Among these genes, however, only Vf has been intensively studied. A positional cloning project led to the identification in the Vf region of a cluster of genes homologous to the Cf resistance genes of tomato and consequently called HcrVfs (homologues to the Cladosporium fulvum resistance genes of the Vf region, Patocchi et al 1999a, b;Vinatzer et al 2001). One of these genes, HcrVf2, when introduced into the susceptible cultivar Gala, conferred apple scab resistance to the transgenic plants, proving the identification of the first apple scab resistance gene (Barbieri et al 2003;Belfanti et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Characterized RLP genes involved in resistance include the Cf genes from tomato (Lycopersicon esculentum) that confer resistance against the fungal pathogen Cladosporium fulvum (Jones et al, 1994;Dixon et al, 1996Dixon et al, , 1998Thomas et al, 1997), tomato Ve genes (Kawchuk et al, 2001), apple (Malus domestica) HcrVf2 (Vinatzer et al, 2001), Arabidopsis (Arabidopsis thaliana) RPP27 (Tö r et al, 2004), and tomato LeEIX1 and LeEIX2 (Ron and Avni, 2004). Developmental RLPs in Arabidopsis include TMM (Yang and Sack, 1995;Nadeau and Sack, 2002), which is involved in stomatal patterning, and CLAVATA2 (CLV2; Jeong et al, 1999) and its maize (Zea mays) ortholog FASCIATED EAR2 (FEA2; Taguchi-Shiobara et al, 2001), which are involved in meristem development.…”
mentioning
confidence: 99%